The Future of Education: Genetic Enhancement and Metahumanities - Sorgner, Stefan Lorenz; Recio Sastre, Alejandro (Revista Ethika+, 2021)
Habermas has criticized the position that educational and genetic enhancements are parallel events (2001, 91). I, on the other hand, will provide reasons for the position that there is a structural analogy between educational and genetic enhancement such that the moral evaluation of these two procedures should be seen as analogous, too. I will show that an affirmation of educational enhancement suggests an affirmation of genetic enhancement. In addition, I offer reasons why both types of enhancement ought to be affirmed. I will progress as follows. First, I will explain the relevance of the question by considering transhumanism and posthumanism. Both are contemporary philosophical and cultural movements in which the question concerning enhancement is central. Second, I will compare educational and genetic enhancement, showing that Habermas’ arguments concerning their relationship are implausible. In the conclusion, I will refer to the relevance of this insight to the future of education, when the humanities will need to be transformed into metahumanities.